Acromegaly: Clinical Care in Central and Eastern Europe, Israel, and Kazakhstan - Bolanowski, Marek; Adnan, Zaina; Doknic, Mirjana; Guk, Mykola; Hána, Václav; Ilovayskaya, Irena; Kastelan, Darko; Kocjan, Tomaz; Kužma, Martin; Nurbekova, Akmaral; Poiana, Catalina; Szücs, Nikolette; et al. (Frontiers in Endocrinology, 2022)
Acromegaly is a rare condition typically caused by benign pituitary adenomas, resulting in excessive production of growth hormone. Clinical manifestations of acromegaly are diverse, varying from the overgrowth of body tissue to cardiovascular, metabolic, and osteoarticular disorders. Symptoms may emerge slowly, overlapping with other diseases and often involve many different healthcare specialists. In the last decade, efforts to provide an accurate and timely diagnosis of acromegaly have improved disease management and clinical experience. Despite this progress, marked differences in the diagnosis, treatment, and management of acromegaly exist from country-to-country. To address these inconsistencies in the region comprising Central and Eastern Europe, Israel, and Kazakhstan, a panel of acromegaly experts from 13 of these countries was convened. Acromegaly experts from each country provided available information on the approaches from their country, including regional treatment centers and multidisciplinary teams, treatment access, reimbursement and availability, and physician education, disease awareness, and patient advocacy. Across several areas of acromegaly management, divergent approaches were identified and discussed, including the provision of multidisciplinary care, approved and available treatments, and disease awareness programs. These were recognized as areas of potential improvement in the management of acromegaly, in addition to participation in national and regional acromegaly registries. Further experience exchange will facilitate the identification of specific strategies that can be adapted in each country, and widespread participation in acromegaly registries will enable their evaluation. It is anticipated that this approach will support the optimization of acromegaly patient care across this region.